DEVELOPMENT OF DIGITAL INFRASTRUCTURE AS THE BASIS OF SUSTAINABLE ECONOMIC GROWTH - Manzura Ibragimovna Azizova (Ecomind Press, 2025)
The development of digital infrastructure is increasingly recognized as a critical driver of sustainable economic growth in both developed and developing economies. In the context of Uzbekistan, where economic modernization and digital transformation are among the top national priorities, investment in digital infrastructure plays a pivotal role in ensuring long-term stability and competitiveness. This article explores the strategic importance of digital infrastructure in stimulating economic growth through enhanced connectivity, innovation, and access to global markets. It examines current trends, governmental policies, and public-private initiatives aimed at accelerating the digital economy. In particular, the study highlights how infrastructure such as broadband internet, data centers, cloud technologies, and digital payment systems serve as enablers for financial inclusion, SME development, and increased productivity across key sectors. Through theoretical and empirical analysis, the paper provides an overview of the challenges and opportunities that Uzbekistan faces in the process of digital infrastructure deployment and proposes policy recommendations to leverage these developments for inclusive and sustainable economic progress.
Keywords: Digital infrastructure, economic growth, innovation, sustainable development, financial inclusion, connectivity, cloud technologies, broadband access, digital transformation.